Disease burden in patients with severe hand, foot, and mouth disease in Jiangsu Province: a cross-sectional study. Issue 5 (30th November 2022) - Han, Ying; Ji, Hong; Shen, Wenqi; Duan, Chunxiao; Cui, Tingting; Chen, Liling; Hang, Hui; Zhang, Zhong; Sun, Hongmin; Zhang, Xuefeng; Jin, Hui
ABSTRACT: This study aimed to estimate the disease burden and health-related quality of life (HRQOL) among patients with severe hand, foot, and mouth disease (HFMD) in Jiangsu Province, China. We analyzed the surveillance data of HFMD cases in Jiangsu Province from 2009 to 2020. Moreover, a cross-sectional study was conducted in Nanjing and Suzhou, China, between January 2017 and May 2018. Patients with severe HFMD and their parents were recruited from selected hospitals. Questionnaires and hospital management systems were used to collect data on direct economic burden. The HRQOL of children was assessed using the TNO-AZL Preschool Quality of Life (TAPQOL) scale. A total of 1, 348, 737 confirmed cases of HFMD were reported to the NNDRS in Jiangsu province during 2009–2020. Of these, 9, 622 were severe cases, with 62 (.64%) of these being fatal. From January 2017 to May 2018, data was collected from 362 severe HFMD cases using a structured questionnaire. The median per capita direct economic burden was RMB 16142.88, and was associated with the region and length of hospital stay ( P < .05). The direct economic burden for all cases of severe HFMD in Jiangsu province between 2017 and 2018 was approximately RMB 16.64 million. Finally, the median (IQR) of the TAPQOL scale for children with severe HFMD was 69.23 (56.20, 82.27). Severe HFMD infection is a relatively large burden for individuals, and the burden of EV-A71 infection was seen to be even greater for the population. Prevention of severe HFMD should strengthen hygiene habits and targeted measures for EV-A71 vaccination.